“Most Lankans are Silent Seethers”: Haunting as Resistance, Spectral Temporality, and “the Dark Heart of Lanka” in The Seven Moons of Maali Almeida - Gajraj, Shreyaa; Kumar, Nagendra (SARE: Southeast Asian Review of English, 2025)
This paper foregrounds Shehan Karunatilaka’s Booker Prize-winning novel The Seven Moons of Maali Almeida’s function as a reflection on the concept of haunting as resistance against forgetting, focusing on the notion of spectral temporality within the context of Sri Lanka itself as a spectral space informed by cultural amnesia. Leveraging Avery Gordon’s framework of ‘haunting’ through her work Ghostly Mattersas a component of social life, and Jacques Derrida’s specterintroduced in his work Specters of Marx, the paper follows traces of absent presences by interrogating the ways in which Sri Lanka’s ghosts demand reclamation of silenced events and delayed justice. This paper argues that The Seven Moons deploys haunting as a mode of political resistance through certain interconnected mechanisms rooted in Sri Lanka’s post-war context: enforced disappearance as state practice, photography as counter archive against institutional erasure, and the figure of Mahakali as expression of collective rage – all grounded in specific “sites of death”. It looks at enforced disappearance as a tool of state terror strategically employed by the Sri Lankan state, alongside laying bare distinctive triggers that actively participate in resisting institutionalized erasure. Finally, it evokes the haunting quality of certain sites of death suggesting their temporal discontinuity.